Actions taken by pedestrians and drivers to avoid accidents - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2000)
A small number of traffic conflicts or potential accidents lead to accidents. Most of road users involved in conflicts do evasive actions to avoid accidents. A research was carried out to examine the actions taken by road users to avoid pedestrian-vehicle collisions or accidents. Information on pedestrian-vehicle conflicts, pedestrian and driver speeds were obtained synchronously through a combination of direct observation, video analysis, and analysis of tube and loop detectors' output. It was found that pedestrians walk faster or run while drivers decelerate to avoid a collision. The decelerations became harder at a point around 25 metres from the stop line and the maximum value was 8.9 m/s'.